Citizen science across borders: employing action design research to identify and address digital skills challenges in the EU through collaborative solutions - Karlis, Valtins; Emilija, Sarma Zane; Bems, Chiaki Sekiguchi; Kouzaridi, Emily; Hing Ting, Karine Lan (Frontiers in Sociology, 2025)
The European University Alliance European University of Technology (EUt+) has endeavored to make a Citizen Lab, as part of the Horizon 2020 project “EXTRAS,” aimed to explore the use of Action Design Research (ADR) methodology for fostering citizen science across boarders and during one of the pilot activities focused on digital skills development. Interactions provided an international forum for educational practitioners from France, Cyprus, and Bulgaria, alongside researchers from the European University of Technology, to collaboratively address the challenges of digital upskilling and reskilling in the European context. Through a series of three workshops, participants engaged in meaningful discussions on the inclusion of diverse identities and intersectionality in digital skill development programs. The ADR framework guided the workshops, facilitating thematic clustering of ideas, generation of design principles, and the cocreation of potential solutions. The findings emphasized the importance of inclusive, identitysensitive approaches to digital skills education, with a focus on adult learners facing various barriers. The workshops were deemed successful in testing the applicability of ADR for citizen science in an international setting, serving as a proof of concept for future Citizen Lab endeavors in diverse contexts and subject areas. The study highlights the potential of Citizen Labs to generate practical and meaningful insights through participatory, cross-border collaboration.